Stability, toxicity, and antibacterial potential of Gallic Acid-Loaded Graphene Oxide (gago) against methicillin-resistant Staphylococcus Aureus (MRSA) strains - Shamsi, Suhaili; Abdul Ghafor, Ahmad Ashraful Hadi; Norjoshukrudin, Nur Hazwani; Ng, Ida May Jen; Abdullah, Siti Nur Sharmila; Sarchio, Seri Narti Edayu; Md Yasin, Faizah; Abd Gani, Shafinaz; Mohd Desa, Mohd Nasir (Dove Medical Press, 2022)
Background: The impetuous usage of antibiotics has led to the perpetual rise of methicillin-resistant Staphylococcus aureus (MRSA), which has garnered the interest of potential drug alternatives, including nanomaterials. Purpose: The present study investigates the stability, toxicity, and antibacterial potential of gallic acid-loaded graphene oxide (GAGO) on several MRSA strains. Methods: The stability of a synthesized and characterized GAGO was monitored in different physiological media. The toxicity profile of GAGO was evaluated in 3T3 murine fibroblast cells and the embryonic zebrafish model. The antibacterial activity of GAGO against MRSA, methicillin-susceptible S. aureus (MSSA), and community-acquired MRSA; with or without Panton-valentine leucocidin gene (MRSA-pvl+ and MRSA-pvl-) was investigated through disk diffusion, CFU counting method, time-kill experiment, and high-resolution transmission electron microscopy (HRTEM) observation. Results: A stable GAGO nanocomposite has shown an improved toxicity profile in 3T3 murine fibroblast cells and zebrafish embryos, besides exhibiting normal ROS levels than graphene oxide (GO) and GA (gallic acid). The nanocomposite inhibited the growth of all bacterial strains employed. The effectiveness of the GAGO nanocomposite was comparable to cefoxitin (CFX), at ≥150 µg/mL in MRSA and MSSA. GAGO exhibited a significantly delayed response towards MRSA-pvl+ and MRSA-pvl-, with increased inhibition following 8 to 24 h of exposure, while comparable activity to native GA was only achieved at 24 h. Meanwhile, for MRSA and MSSA, GAGO had a comparable activity with native GA and GO as early as 2 h of exposure. HRTEM observation further reveals that GAGO-exposed cells were membrane compromised. Conclusion: In summary, the present study indicates the antibacterial potential of GAGO against MRSA strains, but further study is warranted to understand the mechanism of action of GAGO and its resistance in MRSA strains.